2014
DOI: 10.1002/jat.3086
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to 3,3’‐iminodipropionitrile targets late‐stage differentiation of hippocampal granule cell lineages to affect brain‐derived neurotrophic factor signaling and interneuron subpopulations in rat offspring

Abstract: 3,3'-Iminodipropionitrile (IDPN) causes neurofilament (NF)-filled swellings in the proximal segments of many large-caliber myelinated axons. This study investigated the effect of maternal exposure to IDPN on hippocampal neurogenesis in rat offspring using pregnant rats supplemented with 0 (controls), 67 or 200 ppm IDPN in drinking water from gestational day 6 to day 21 after delivery. On postnatal day (PND) 21, female offspring subjected to analysis had decreased parvalbumin(+), reelin(+) and phospho-TrkB(+) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Developmental exposure to IDPN has also been shown to cause morphometric changes in hippocampal structures (Zmarowski et al, 2012). With regard to the developmental neurotoxicity of IDPN, we previously found that maternal exposure to IDPN reversibly disrupted neurogenesis targeting late-stage differentiation of granule cell lineages in the dentate gyrus in rat offspring (Itahashi et al, 2015). However, we have recently found that maternal IDPN exposure in mice affected hip-pocampal neurogenesis, increasing the number of postmitotic granule cells involving glutamatergic signals at the end of maternal exposure, and then suppressing SGZ cell proliferation to result in reduction of the broad range of the granule cell lineage population in offspring (Hasegawa-Baba et al, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…Developmental exposure to IDPN has also been shown to cause morphometric changes in hippocampal structures (Zmarowski et al, 2012). With regard to the developmental neurotoxicity of IDPN, we previously found that maternal exposure to IDPN reversibly disrupted neurogenesis targeting late-stage differentiation of granule cell lineages in the dentate gyrus in rat offspring (Itahashi et al, 2015). However, we have recently found that maternal IDPN exposure in mice affected hip-pocampal neurogenesis, increasing the number of postmitotic granule cells involving glutamatergic signals at the end of maternal exposure, and then suppressing SGZ cell proliferation to result in reduction of the broad range of the granule cell lineage population in offspring (Hasegawa-Baba et al, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…[31][32][33] Iminodipropionitrile is also known to damage or impair the function of various sensory systems, including olfactory, 34 auditory, 35 and visual 36 systems. Subsequent researches have shown that IDPN is not only toxic to sensory, vestibular, and nervous systems but also causes reproductive, 37 developmental, 38 and hepatic 39 toxicities. The magnitude of IDPN-induced hepatotoxicity in mice was independent of the severity of vestibular epithelial damage.…”
Section: Introductionmentioning
confidence: 99%